Numerical Thermodynamic Analysis of Two-Phase Solid-Liquid Abrasive Flow Polishing in U-Type Tube. (26th August 2014) - Li, Junye; Yang, Zhaojun; Liu, Weina; Qiao, Zemin
Abstract : U-type tubes are widely used in military and civilian fields and the quality of the internal surface of their channel often determines the merits and performance of a machine in which they are incorporated. Abrasive flow polishing is an effective method for improving the channel surface quality of a U-type tube. Using the results of a numerical analysis of the thermodynamic energy balance equation of a two-phase solid-liquid flow, we carried out numerical simulations of the heat transfer and surface processing characteristics of a two-phase solid-liquid abrasive flow polishing of a U-type tube. The distribution cloud of the changes in the inlet turbulent kinetic energy, turbulence intensity, turbulent viscosity, and dynamic pressure near the wall of the tube were obtained. The relationships between the temperature and the turbulent kinetic energy, between the turbulent kinetic energy and the velocity, and between the temperature and the processing velocity were also determined to develop a theoretical basis for controlling the quality of abrasive flow polishing.